The COVID-19 outbreak and implications for the Tokyo 2020 Summer Olympic Games - Gallego, V.; Nishiura, H.; Sah, R.; Rodriguez-Morales, A. J. (Travel Medicine and Infectious Disease, 2020)
Mass meetings, such as the Olympic Games, require considerable preparation and responsiveness by the host country. Globally, the WHO has a strategic preparedness and response plan for the coronavirus [23]. It is too early to realistically discuss the future course of epidemic. Scientists do not believe that a related COVID-19 epidemic will spread rapidly and intensively in Japan, but the scientific community around the world must be prepared to diagnose early and provide the necessary epidemiological data so that prevention measures and appropriate decisions are made regarding the Tokyo 2020 Olympic and Paralympic Games.